17-{35-[18-16(x+y)÷4÷2]÷3×2-5}÷8×3=11
scadem 17
-{35-[18-16(x+y)÷4÷2]÷3×2-5}÷8×3= -6
inmultim cu -1 ca sa scapam de -
{35-[18-16(x+y)÷4÷2]÷3×2-5}÷8×3=6
impartim la 3
{35-[18-16(x+y)÷4÷2]÷3×2-5}÷8=2
inmultim cu 8
35-[18-16(x+y)÷4÷2]÷3×2-5= 16
scadem 35
-[18-16(x+y)÷4÷2]÷3×2-5= -19
inmultim iar cu -1
[18-16(x+y)÷4÷2]÷3×2-5=19
adunam 5
[18-16(x+y)÷4÷2]÷3×2=24
impartim la 2
[18-16(x+y)÷4÷2]÷3=12
inmultim cu 3
18-16(x+y)÷4÷2= 36
scadem 18
-16(x+y)÷4÷2= 18
inmultim cu 2
-16(x+y)÷4= 36
inmultim cu 4
-16(x+y)= 144
impartim cu -16
x+y= 9